ON THE PERFORMANCE OF GNSS LEVELLING OVER STEEP SLOPES - ERENOGLU, R. CUNEYT; YUCEL, MEHMET ALI; PIRTI, ATINC; SANLI, D. UGUR (Boletim de Ciências Geodésicas, 2012)
In geodetic applications variety, one of the main current focuses is recently to determine the heights of ground stations with high accuracy. Specially the possibility of acquiring 3D information of the point positioning with high accuracy is opening up new strategies of investigating the heighting. Global Navigation Satellite System (GNSS) for 3D positioning is undergoing rapid developments and GNSS heighting can be an alternative to terrestrial techniques of height measurements. This paper presents a research study on the use of GNSS heighting in the case of steep slopes and multipath issue. Short baseline solution strategies were performed by using Bernese Software v. 5.0. The analysis results are also compared to the results of techniques of the terrestrial levelling. The results show that GNSS can be used as an practical surveying method to the terrestrial levelling with comparable accuracies. Furthermore, one can save up to 1 hour using GNSS instead of geometric levelling over a steep slope of a 100 m. On the other hand, as usual multipath is the primary error source decreasing the efficiency of GNSS, and it has been studied experimentally in this paper.